2017
DOI: 10.1126/science.aan0516
|View full text |Cite
|
Sign up to set email alerts
|

Potent peptidic fusion inhibitors of influenza virus

Abstract: Influenza therapeutics with new targets and mechanisms of action are urgently needed to combat potential new pandemics, emerging viruses, and constantly mutating circulating strains. We report here on design and structural characterization of potent peptidic inhibitors against influenza hemagglutinin (HA). The peptide design was based on complementarity determining region (CDR) loops of anti-HA human broadly neutralizing antibodies, FI6v3 and CR9114. The optimized peptides exhibit nanomolar affinity and neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(156 citation statements)
references
References 40 publications
3
153
0
Order By: Relevance
“…The structures of HA in complex with broadly neutralizing antibodies targeting the conserved stem region (Ekiert et al, 2009) (Figure 2), which neutralize by blocking the fusogenic conformational change, have shown us how to use the complementarity determining region of the bound antibodies to design small proteins targeting the same site (Fleishman et al, 2011). Further studies identified small peptides targeting this site, with the same potent inhibitory effect (Kadam et al, 2017). These results suggest that it may be possible to identify non-peptidic, orally bioavailable antiviral compounds using the same strategy to treat flu infections.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of HA in complex with broadly neutralizing antibodies targeting the conserved stem region (Ekiert et al, 2009) (Figure 2), which neutralize by blocking the fusogenic conformational change, have shown us how to use the complementarity determining region of the bound antibodies to design small proteins targeting the same site (Fleishman et al, 2011). Further studies identified small peptides targeting this site, with the same potent inhibitory effect (Kadam et al, 2017). These results suggest that it may be possible to identify non-peptidic, orally bioavailable antiviral compounds using the same strategy to treat flu infections.…”
Section: Discussionmentioning
confidence: 99%
“…Two other stem-binding bnAbs, FI6v3 44 and 39.29 58 of the V H 3–30 germline family, which bind the HA at a very different angle and use both light and heavy chains for interaction, compared to V H 1–69, where the heavy chain makes the majority, if not all, of the stem interactions. Nonetheless, V H 1–69 and V H 3–30 antibodies have very similar binding footprints and fill the same set of hydrophobic pockets in the HA stem 59 . However, the V H 3–30 family uses an extended CDR H3 to occupy the same pockets as the IFY motif of the V H 1–69 antibodies.…”
Section: Design Of a More Universal Vaccinementioning
confidence: 97%
“…In another recent breakthrough, small peptides were designed and characterized against this same site in the HA stem, also based on how bnAbs target the stem, in a collaboration between Janssen and our laboratory 59 . Using the CDR interacting loops of two bnAbs FI6v3 and CR9114 as templates, cyclic peptides that also incorporated non-proteinogenic amino acids were designed to fill the same hydrophobic pockets in the HA stem as the stem-binding bnAbs 59 .…”
Section: Design Of Small Proteins and Peptides Against The Ha Stem Domentioning
confidence: 99%
See 2 more Smart Citations